Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
ZenodoArchiveID: 5652141 previousDOI: 10.5281/zenodo.4762283 previousDOI: 10.5281/zenodo.4762283 2405685:UQSMRFBF previousDOI: 10.5281/zenodo.3407498 EdTechHub.Source: DOI: DOI:10.5281/zenodo.4762283 2405685:UQSMRFBF EdTechHub.Source: <this> shortDOI: 10/ghgnd8 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407498 10.5281/zenodo.5652141 10/ghgnd8 2129771:U3XSZB5F 2339240:CRCGCNE9 2405685:UQSMRFBF
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652140 previousZenodoArchiveID: 3936687 previousshortDOI: 10/ghgnd2 previousDOI: 10.5281/zenodo.3936687 shortDOI: 10/ghgnd2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3936687 10.53832/edtechhub.0037 10/ghgnd2 2339240:EHTSKIBR 2339240:YQHNWNMB 2405685:5P5HVP47 2405685:BBP57X2K 2405685:SKFMQF3F 2405685:XI5PXVB3
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

Is there Learning Continuity during the COVID-19 Pandemic? A Synthesis of the Emerging Evidence - McBurnie, Chris; Adam, Taskeen; Kaye, Tom (Journal of Learning for Development, 2020)
Since the onset of COVID-19, governments have launched technology-supported education interventions to ensure children learn. This paper offers a narrative synthesis of emerging evidence on technology-based education to understand the current experiences of learners, teachers and families. Studies find that few students in low- and middle-income countries have access to technology-supported learning with the most marginalised children appearing to have the least educational opportunities. As such, the education response to COVID-19 could widen existing inequalities.
KerkoCite.ItemAlsoKnownAs: 2405685:WFEBLP79
Keywords: dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No DOI found